The Integration of the Eastern Partnership Countries’ Digital Markets into the EU Digital Single Market - Ivasechko Olha; Tsebenko Oleh; Turchyn Yaryna; Yanina Viktoriia (Politics in Central Europe)
The aim of the article is to analyse the motives for integrating the digital markets of the Eastern Partnership countries into the EU Digital Single Market, as well as the challenges and opportunities that this integration creates. The EU Roadmap ‘Digital Compass 2030’, i.e. the Union’s strategic goals for Europe’s digital sovereignty, was highlighted. The position of each of the recipient countries of the EaP in the digitalisation indices was represented. The issues and prospects of the integration of digital markets of the Eastern Partnership countries on the way to the EU Digital Single Market were pinpointed. It was proved that both the EU and the member states of the EaP are striving to remain competitive and to not be outsiders of technological transformations. The motivation for the integration of the digital markets of these countries into the Digital Single Market of the EU is, above all, the desire to be a full member of the Community.